Synthesis of heavy cyanide analogs for the design of novel Prussian blue analogs - Yang, E (2023)
This thesis describes the chemistry of metal complexes of the cyaphide ion (C≡P−) and some of its derivatives, including their syntheses, properties, and reactivity.